2012
DOI: 10.1093/cercor/bhs179
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Tactile Temporal-Order Judgment in Humans: an fMRI Study

Abstract: Little is known about the neuronal mechanisms underlying the temporal ordering of tactile signals. We examined the brain regions involved in judgments of the temporal order of successive taps delivered to both hands. Participants received identical stimuli while engaging in 2 different tasks: Judging the temporal order and judging the numerosity of points of tactile stimulation. Comparisons of the functional magnetic resonance imaging data obtained during the 2 tasks revealed regions that were more strongly ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 60 publications
7
77
0
Order By: Relevance
“…Similarly, spatial judgments about the numerosity of pins lifted to induce two tactile stimuli, one applied to each hand, were not influenced by posture (Takahashi et al, 2012). In contrast, in our secondary tasks, crossing effects emerged for temporal as well as for spatial judgments about the stimuli's vibration types.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Similarly, spatial judgments about the numerosity of pins lifted to induce two tactile stimuli, one applied to each hand, were not influenced by posture (Takahashi et al, 2012). In contrast, in our secondary tasks, crossing effects emerged for temporal as well as for spatial judgments about the stimuli's vibration types.…”
Section: Discussionmentioning
confidence: 46%
“…Finally, response accuracy in the secondary task was again influenced by posture, that is, a crossing effect emerged in both tasks. Notably, in previous studies, a crossing effect was not reported in similar tasks (Roberts and Humphreys, 2008;Takahashi et al, 2012).…”
Section: Discussionmentioning
confidence: 77%
“…Bernasconi et al (2010aBernasconi et al ( , 2010b) demonstrated the importance of activity in the posterior sylvian regions in auditory TOJ by investigating auditory-evoked potentials. Recently, brain regions involved in judgments of temporal order of two tactile stimuli were examined (Takahashi et al, 2013), and authors purposed that the temporal order of tactile signals could be determined by combining spatial representations of stimuli in the parietal and prefrontal cortices (Macaluso and Driver, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows the resulting reconstructed stimulation sites over the superior parietal lobule in the left and right PPC. These sites are in close proximity to regions shown to be activated by the behavioral task (Takahashi et al 2013) and to the sites used in several TMS studies in which the PPC was targeted (e.g., Della-Maggiore et al 2004; Vesia et al 2008).
Fig.
…”
Section: Methodsmentioning
confidence: 77%
“…Each of these studies demonstrated that the posterior parietal cortex (PPC) showed greater activity associated with the remapping process when the arms were in a crossed posture (Lloyd et al 2003; Takahashi et al 2013; Wada et al 2012). The current study sought to determine the functional necessity of the PPC involvement by using single-pulse transcranial magnetic stimulation (TMS) to temporarily disrupt neural processing in either the right or left PPC, while participants performed the vibrotactile TOJ task with the hands in either an uncrossed or crossed configuration.…”
Section: Introductionmentioning
confidence: 99%